Factors Affecting Mold Growth in Homemade Bread Using Factorial Design - Chan, Boon Hui; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2026)
Homemade bread is considered healthier than commercial bread due to absence of chemical preservatives and additives. However, its high moisture content leads to mold growth and short shelf life. This study aimed to determine how combinations of preservative types, moisture conditions and storage conditions influence mold growth in homemade bread using a 3³ factorial design. Also, to evaluate the main and interaction effects of these factors through Analysis of Variance (ANOVA). The experiment involved three factors at three levels each, producing 27 treatment combinations, replicated to yield 81 samples. The response variable was the number of days until mold fully cover the bread surface. ANOVA was conducted to identify significant factors affecting mold growth and model adequacy checks were performed to validate reliability. Results indicated that all three factors significantly affected the mold growth. Storage condition had the strongest effect, followed by preservative types and moisture condition. bread treated with a chemical preservative, without water sprinkling and stored in open air exhibited the longest mold-free duration up to 27 days. While bread without preservative, sprinkled once every five days and stored fully covered showed the shortest shelf life about 9 days. Interaction effect revealed that there has significant effect for combinations of preservative types with storage conditions and moisture conditions with storage conditions. Overall, the study demonstrates that shelf life of bread can improved through combinations of preservative types, moisture conditions and storage conditions. For further study, it should include sensory evaluation and different preservative types to improve shelf-life prediction of homemade bread.